Dietary Inclusion of Tinospora Cordifolia (Giloy) Stem Powder on Performance,Serum Parameters and Carcass Traits of Japanese Quails - CH.Agnivesh, D.Rambabu; Gurram, Srinivas; J.Narasimha (Indian Journal of Animal Nutrition, 2024)
This study was conducted to evaluate the effect of Giloy stem powder (Tinospora cordifolia) on the performance of Japanese quails. 480-day old Japanese quail chicks randomly distributed into six dietary treatments with four replicates per treatment and each replicate had twenty birds. The first group was kept as a control (T1) and given the control diet (CD) without antibiotic while second group (T2) was fed CD with antibiotic, third (T3), fourth (T4), fifth (T5) and sixth (T6) groups were fed CD supplemented with Giloy stem powder @ 0.25, 0.50, 0.75 and 1% respectively. The results indicated that supplementation of Giloy stem powder @ 0.50% (T4) recorded significantly (P